Digital Module Innovation in Multimedia Lectures with a Project-Based Learning Model - Rini Marwati; Kartika Yulianti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
The use of multimedia as a medium of information has been utilized in various fields, including in lectures at universities. This paper discusses the development of a digital module for Multimedia lectures with a Project-Based Learning model. The research method used is research and development. The research results show that the developed digital module effectively facilitates students in completing their projects. Students succeeded in creating mathematics learning content for high school students packaged in a Learning Management System (LMS). Furthermore, 90% of students gave a positive response to Project-Based Learning lectures using the developed digital module.